- Segmentasi Pelanggan Shopee di Kotamadya Pontianak Berdasarkan Preferensi Metode Pembayaran COD Cek Dulu: - - wahyudi, hijrah; -, Mardiyati (Jurnal Ekonomi STIEP, 2024)
One of the largest e-commerce platforms in Southeast Asia, Shopee, has implemented the COD Cek Dulu payment method for buyers across Indonesia who meet certain terms and conditions. SPX Hemat, SPX Sameday (Seller Managed by Shopee), and SPX Standard allow for local returns for the COD Cek Dulu payment method, aiming to enhance buyer trust and attract new customers. Buyers can open packages before making payment and can return COD Cek Dulu packages if the products do not match the description or photos provided. This study aims to describe the segmentation of Shopee customers in Pontianak City from the perspective of the COD Cek Dulu payment method. The research concludes that the customer segmentation of Shopee users employing the COD Cek Dulu method in Pontianak City shows that there are consumers categorized as liking the brand and committed buyers. However, there are also consumers classified as switcher buyers, habitual buyers, and satisfied buyers. This presents a challenge for Shopee's management to consistently enhance customer satisfaction, thereby strengthening customer loyalty. One limitation of this study is the relatively small number of respondents involved.